Otoritas Orang Tua Dalam Memaksa Kawin Anak Usia 21 Tahun Ditinjau Dari Kompilasi Hukum Islam - Abdullah Sani Kurniadinata; Alang Sidek (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
This study aims to determine the authority of parents in forcing the marriage of children aged 21 years and to find out the review of the Islamic Law Compilation regarding the authority of parents in forcing the marriage of children aged 21 years. This type of research is a qualitative research with a field research approach. The object of the research is people who are forced to marry, accompanied by information from the parents of the children and the opinions of some people in the village of Sibual buali, Kec. Ulu Barumun Kab. Palas. Data were collected using observation and interview techniques, where the researcher stopped collecting data when enough data had been collected. The conclusion from this study is that the authority of parents in forcing the marriage of 21-year-old children in the village of Sibual Buali is motivated by several factors, namely the wishes of parents, in this case due to several reasons such as parental concerns that the child is not married, getting an irresponsible companion and closer family ties. Meanwhile, a review of the compilation of Islamic law regarding the authority of parents in forcing the marriage of a 21-year-old child negates the father's right of ijbar to his child in accordance with Article 16 paragraphs 1 and 2 which explains that marriage is based on the consent of the prospective bride and groom, and the form of consent of the prospective bride can be in the form of a firm statement and manifest in writing, verbally, or with signs but can also be silent in the sense that there is no firm objection. Keywords: Parental Authority, Forced Marriage, Compilation of Islamic Law